Role Of Neuron-Specific Enolase and Ferritin in Neuroblastoma and Wilms Tumor - Jwda, Nihad Atea; Rasheed, Manal Kamal; Ghali, Hasanein Habib (Journal of Neonatal Surgery, 2025)
The role of enolase isozymes and ferritin as biomarkers in pediatric solid tumors, including neuroblastoma and Wilms tumor. While neuron-specific enolase (NSE) is well-established in neuroendocrine tumors, its expression patterns and prognostic significance in other childhood cancers remain underexplored. Similarly, ferritin, traditionally linked to iron metabolism and inflammation, may have unrecognized associations with tumor aggressiveness or treatment response in these malignancies. dysregulated enolase isoforms and altered ferritin levels correlate with disease progression, metastatic potential, or therapeutic outcomes in pediatric solid tumors. Patient and methods: This case-control study, conducted at Baghdad Teaching Hospital (February–December 2024), evaluated Neuron-Specific Enolase (NSE) and ferritin as potential biomarkers in pediatric solid tumors. The study included 98 children under 10 years old, divided into three groups: 34 neuroblastoma patients, 31 Wilms tumor patients, and 33 healthy controls. Serum levels of NSE and ferritin were measured using Sandwich ELISA. This case-control study evaluated serum neuron-specific enolase (NSE) and ferritin levels in pediatric solid tumors. Neuroblastoma patients exhibited dramatically elevated NSE (424.71±326.17 ng/mL; 43-fold higher than controls, p<0.001) and significantly higher levels than Wilms tumor cases (175.45±97.41 ng/mL, p<0.001). Conversely, Wilms tumor patients showed the highest ferritin levels (505.84±266.58 μg/L; 7.9-fold above controls, p<0.001), significantly exceeding neuroblastoma values (324.12±138.11 μg/L, p<0.001). These findings demonstrate distinct biomarker profiles: NSE shows exceptional elevation in neuroblastoma, while ferritin is markedly increased in Wilms tumor, suggesting their potential diagnostic utility in differentiating these pediatric malignancies